Analysis of Teacher Candidate Responses to the Needs of Blended Learning Model Based on MOOCs and Augmented Reality - Eko Risdianto; Kusen Kusen; Murni Yanto; Yuyun Yumiarty (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
The article aims to analyze the response to the need for a blended learning model based on MOOCs and augmented reality for prospective teachers. The sample data were 52 prospective teachers. The instrument used in this study was a questionnaire sheet for the needs of prospective teachers. The results of this study indicated that the instruments used are valid and reliable. It was evidenced by the results of the validity calculation which states that 18 questions were valid and no questions were issued. Then, the calculation of data reliability using the Cronbach alpha method with a score of 0.878, this value was greater when compared with the rtable value for α = 0.05, namely 0.273. Hence, it can be said that the data used reliable. For the percentage of prospective teacher needs, 88.86% was obtained, which means that prospective teachers strongly agree that the need for a blended learning model based on MOOCs and augmented reality for prospective teachers Keywords: Teacher Candidate Response, MOOCs, Augmented Reality, Blended Learning